HUBUNGAN TINGKAT PENGETAHUAN IBU MENYUSUI TENTANG ASI DENGAN POLA PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS NGETOS KABUPATEN NGANJUK - Titin Ratnaningsih; Puji Astutik; Tri Retnoningsih (JURNAL SABHANGA, 2025)
Mother’s milk (ASI) is the only natural food source that needs to be protected and promoted.Recently, there is tendency of decreasing mother’s milk (ASI) giving replaced by PASI or formula milk. Itworriedly will extend to rural area and will have negative impact. This research has a purpose to knowrelationship of suckling mother knowledge level about ASI with pattern of giving Exclusive ASI inGovernment Clinic (Puskesmas) of Ngetos. This research uses analytic observational method by using crosssectional approach. The sample established with purposive sampling with respondent number of 46 people.Identification result of this research suggested that most suckling mother knowledge level about ASI is lessgood (64.5%), whereas pattern assessment of giving ASI suggested that 69.6% mother who does not givesuckles exclusively ASI. From result of statistic analysis, chi-square tests by using continuity correction(a),p=0.000 is taken. This means that there is significant relationship between suckling mother knowledge levelabout ASI and pattern of giving exclusive ASI in working area of Local Government Clinic (Puskesmas)of Ngetos